A, the Development and Training of an Office Facilities Damage Complaint Service System - Disa, Syaharullah; Madao, Hiknatius Rianto; Maharani, Ezra; Wanda, Juli (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2024)
The problem faced in the process of reporting damage to facilities at the LLDIKTI Region IX Office is that the process is still manual, where officers have to survey directly and record the damage manually so that it does not run effectively and efficiently. The aim of developing the system is to facilitate the facility complaint process and record damage to facilities for employees and guests, as well as making it possible to print facility damage reports online. The complaint service system was developed using the PHP and HTML programming languages, and uses a framework and MySQL as a data storage system. Application development uses object-oriented development methods. Through this web-based application, users can complain about damaged facilities. Officers can print monthly records regarding damage to office facilities by utilizing computerized data. So that it is more efficient and effective in handling damage to facilities